2007
DOI: 10.1002/jts.20237
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a screening instrument for posttraumatic stress disorder in a community sample of Bedouin men serving in the Israeli Defense Forces

Abstract: This study evaluates the performance of the Screen for Posttraumatic Stress Disorder (SPTSS) in the assessment of a high-risk ethnic minority sample. Participants included 317 Bedouin men serving in the Israeli Defense Forces (IDF), who disclosed extensive trauma and loss. The sensitivity and specificity of the SPTSS were calculated using the Structured Clinical Interview for DSM-IV (SCID) as the criterion for posttraumatic stress disorder (PTSD), which was diagnosed in 14.5% of respondents. Receiver operating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…Participants had a mean score of 3.18 on the SPTSS, ranging from a minimum of .7 to a maximum of 7.29. Although standard data for the SPTSS are not available as a criterion for the diagnosis of PTSD in Brazil, it is notable that an international study (Caspi, Carlson, & Klein, 2007) found a cutoff point for diagnosis of PTSD of an SPTSS score above 7.41.…”
Section: Event Centrality and Screening Of Ptsd Symptomsmentioning
confidence: 99%
“…Participants had a mean score of 3.18 on the SPTSS, ranging from a minimum of .7 to a maximum of 7.29. Although standard data for the SPTSS are not available as a criterion for the diagnosis of PTSD in Brazil, it is notable that an international study (Caspi, Carlson, & Klein, 2007) found a cutoff point for diagnosis of PTSD of an SPTSS score above 7.41.…”
Section: Event Centrality and Screening Of Ptsd Symptomsmentioning
confidence: 99%
“…This brief, 17-item, self-report instrument is not keyed to a single event, and rated on a 10-point scale from never (0) to always (10) in response to "how much that thing has happened to you during the past two weeks." Performance of the Screen for Posttraumatic Stress Symptoms in the men's sample indicated equal sensitivity and specificity rates of 89% vis-à-vis a SCID diagnosis of PTSD, at a cut point of 5.50 (Caspi al., 2007). Internal consistency of the scale in the women's sample was very good (α = .94).…”
Section: Methodsmentioning
confidence: 98%
“…One may conclude that the combination of stressed life in a conflict area and the elevation of psychiatric morbidity might lead to elevated mental health services utilization. Among respondents with diagnosed disorders, the rate of help seeking for mental health services was lower among Arab-Israelis than among Jewish-Israelis [6,7]. The low mental health utilization rate among minorities in Israel probably emanates from stigmatization, social and cultural norms regarding the use of mental health and help seeking.…”
Section: Introductionmentioning
confidence: 99%
“…It is likely that there are many Arab minorities whose posttraumatic reactions remain undetected and untreated. Moreover, the research body in mental health utilization among minorities after armed conflict is scarce [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation